The influence of the Crusades on European military architecture to the end of the twelfth century - Lawrence, TE (1910)
Any consideration of the influence of Levantine military architecture on that of the West must almost of necessity be minute and technical; and any such enquiry must obviously be based on first-hand study of the actual remains of 12th. century castles in Syria and Europe. A few of the castles in the East have been adequately described with plans and illustrations, but beyond these there are many, often of equal importance, of which details have never been published; and the sites of some, which figure in history, remain unidentified in the riot of hills filling up Syria between Antioch and Nazareth. Reference is here made to some forty Crusading castles, including, for the 12th. century, nearly all those in the East. The materials for the 13th. century in Armenia and the Greek islands are almost entirely unworked; there has, as a matter of fact, been practically no exhaustive study even of the castles of that period in Europe. [continued in thesis]